Temperature dependent elastic properties of nanocrystalline Co1−xZnxFe2O4. (December 2015) - Sadhana, K.; Sandhya, R.; Murthy, S.R.; Praveena, K.
Abstract: Nanocrystalline Co1− x Zn x Fe2 O4 (0≤ x ≥1) powders were synthesized using the microwave hydrothermal method at different synthesis conditions. The synthesized powders were characterized by XRD and TEM. The average particle size was obtained from TEM and it is found to be 17 nm. Then the powders were sintered using the microwave sintering method at 900 °C/15 min. A detailed study of elastic behavior of Co0.4 Zn0.6 Fe2 O4 has been undertaken using a composite piezoelectric oscillator method over a temperature range of 300–600 K. The elastic modulus of all the ferrites was found to decrease with an increase in the temperature, except near the Curie temperature ( T C ), where a small anomaly is observed. The above observations were carried in the demagnetized state; the application of a 380 mT magnetic field allowed us to reach the saturated state of the sample at any one of the measuring temperatures. The anomaly observed in the thermal variation of elastic moduli is qualitatively explained with the help of temperature variation of magneto-crystalline anisotropy constant.